Patient Factors Contributing to Variation in Same-Hospital Readmission Rate. (June 2015) - Henke, Rachel Mosher; Karaca, Zeynal; Lin, Hollis; Wier, Lauren M.; Marder, William; Wong, Herbert S.
The Centers for Medicare & Medicaid Services Hospital Readmission Reduction Program and the Centers for Medicare & Medicaid Innovations Bundled Payments for Care Improvement Initiative hold hospitals accountable for readmissions that occur at other hospitals. A few studies have described the extent to which hospital readmissions occur at the original place of treatment (i.e., same-hospital readmissions). This study uses data from 16 states to describe variation in same-hospital readmissions by patient characteristics across multiple conditions. We found that the majority of 30-day readmissions occur at the same hospital, although rates varied considerably by condition. A significant number of hospitals had very low rates of same-hospital readmissions, meaning that the majority of their readmissions went to other hospitals. Future research should examine why some hospitals are able to retain patients for a same-hospital readmission and others are not.